Specific immunotherapy ameliorates ulcerative colitis. Issue 1 (December 2016) - Cai, Min; Zeng, Lu; Li, Lin-Jing; Mo, Li-Hua; Xie, Rui-Di; Feng, Bai-Sui; Zheng, Peng-Yuan; Liu, Zhi-Gang; Liu, Zhan-Ju; Yang, Ping-Chang
Abstract Background Hypersensitivity reaction to certain allergens plays a role in the pathogenesis of inflammatory bowel disease (IBD). This study aims to observe the effect of specific immunotherapy in a group of IBD patients. Methods Patients with both ulcerative colitis (UC) and food allergy were recruited into this study. Food allergy was diagnosed by skin prick test and serum specific IgE. The patients were treated with specific immunotherapy (SIT) andClostridium butyricum (CB) capsules. Results After treating with SIT and CB, the clinical symptoms of UC were markedly suppressed as shown by reduced truncated Mayo scores and medication scores. The serum levels of specific IgE, interleukin (IL)-4 and tumor necrosis factor (TNF)-α were also suppressed. Treating with SIT alone or CB alone did not show appreciable improvement of the clinical symptoms of UC. Conclusions UC with food allergy can be ameliorated by administration with SIT and butyrate-production probiotics.